Low cost and high performance UPQC with four-switch three-phase inverters - Trinh, Quoc-Nam (2015)
This paper introduces a low cost, high efficiency, high performance three-phase unified power quality conditioner (UPQC) by using four-switch three-phase inverters (FSTPIs) and an extra capacitor in the shunt active power filter (APF) side of the UPQC. In the proposed UPQC, both shunt and series APFs are developed by using FSTPIs so that the number of switching devices is reduced from twelve to eight devices. In addition, by inserting an additional capacitor in series with the shunt APF, the DC-link voltage in the proposed UPQC can also be greatly reduced. As a result, the system cost and power loss of the proposed UPQC is significantly minimized thanks to the use of a smaller number of power switches with a lower rating voltage without degrading the compensation performance of the UPQC. Design of passive components for the proposed UPQC to achieve a good performance is presented in detail. In addition, comparisons on power loss, overall system efficiency, compensation performance between the proposed UPQC and the traditional one are also determined in this paper. Simulation and experimental studies are performed to verify the validity of the proposed topology.